Effect of drying treatments of Philippine Serpentina (Andrographis paniculata) tea leaves on its antioxidant activity and bioactive compound concentrations - Cacayan, Ezra Gabrielle J.
The study aimed to determine the effect of different thermal drying methods (i.e., oven-drying, microwave-drying, and cabinet-drying) and their drying parameters (i.e., drying time and temperature) on Andrographis paniculata (AP) leaves by evaluating antioxidant activity and bioactive compound concentration of the produced AP extracts. Samples were dried using the three drying methods at 50ºC, 1000W, and 50ºC, respectively, until constant moisture content loss, and were then extracted with methanol. DPPH and ABTS assays were conducted to evaluate antioxidant activities, using IC50 as a parameter, and the IC50 of cabinet-dried samples for DPPH (5.613) and ABTS (4.040) were found to be significantly lower (p < 0.05) than the other two drying methods, indicating that cabinet-dried samples had the highest antioxidant activity. This result is likely attributed to the system’s exhaust, allowing better temperature control throughout the drying time. The effect of different temperatures (30ºC, 40ºC, 50ºC, 60ºC, and 70ºC) and necessary drying times of cabinet-drying were then evaluated based on the retention of total phenolic content (TPC) and total flavonoid content (TFC). A nonlinear trend was observed for both compounds. Their contents were found to be lowest at 30ºC, increasing with rising temperatures and shorter drying times, and peaking at 50ºC before eventually falling to a continuous decline. This trend implies that the drying conditions are optimal when there is a balance between minimizing the adverse effects of heat and processing time. Pearson’s correlation analysis also revealed that temperature has a moderate positive correlation with phenolic content (r = 0.5838211), and a high positive correlation with flavonoid content (r = 0.7715358), indicating that flavonoids are more heat-sensitive than phenols. Overall, cabinet-drying at 50ºC can potentially be used for the commercial production of A. paniculata tisane due to its effective retention of antioxidant activity and compounds.